Campus Sewage Treatment by Golenkinia SDEC-16 and Biofuel Production under Monochromic Light. (19th March 2020) - Nie, Changliang; Jiang, Liqun; Yu, Ze; Yang, Zhigang; Hou, Qingjie; Pei, Haiyan
Abstract : The integration of microalgal cultivation in wastewater can fulfill the dual roles of pollutant degradation and biomass output. Meanwhile, the LED lights with different wavelengths have a great effect on the growth and metabolism of microalgae. In this study, Golenkinia SDEC-16, a strain isolated for biofuel production, was evaluated to verify its potentials for campus sewage treatment and lipid accumulation under the red, green, and blue lights. The results indicated that the treated campus sewage met the first grade level in the Chinese pollutant discharge standards for municipal wastewater treatment plants within seven days under both red and blue light. The green light failed to exhibit excellent performance in nutrient removal, but facilitated the lipid synthesis as high as 42.99 ± 3.48%. The increased lipid content was achieved along with low biomass accumulation owing to low effective light utilization, indicating that the green light could be merely used as a stimulus strategy. The red light benefited the photosynthesis of Golenkinia SDEC-16, with the maximal biomass concentration of 0.80 ± 0.03 g/L and lipid content of 36.90 ± 3.62%, which can attain the optimal balance between biomass production and lipid synthesis.